Wakaf dalam Perspektif Tafsir Al-Qur’an dan Hadis Ahkam: Analisis Normatif dan Implikasinya terhadap Hukum Islam Kontemporer - Ifham, Dhiyaul Habib; Yuslem, Nawir; Zein, Achyar (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This article examines waqf from the perspective of Qur’anic exegesis and hadith ahkam to clarify its normative foundations and implications for contemporary Islamic law. Although the term waqf is not explicitly mentioned in the Qur’an, its core principles are embedded in verses concerning infaq, sadaqah, and the management of wealth for public benefit. This study employs a qualitative library research method using a descriptive-analytical approach to classical and contemporary Qur’anic commentaries, as well as authoritative collections of legal hadith. The findings indicate that the Qur’an provides the ethical and normative framework of waqf through the principle of sustainable charity, while hadith ahkam offer concrete legal legitimacy, particularly through the concept of sadaqah jariyah and the practice of waqf initiated by the Prophet’s companions. From the perspective of maqāṣid al-sharī‘ah, waqf functions as a strategic legal instrument to promote social justice, protect wealth, and ensure long-term public welfare. The study further argues that contextual interpretation of Qur’anic verses and hadith supports the development of contemporary waqf practices, including productive and cash waqf, as long as they remain consistent with sharia principles. Therefore, integrating Qur’anic exegesis and hadith ahkam is essential to strengthening the legitimacy and adaptability of waqf within modern Islamic legal frameworks.